On the history of university statistics - Sheynin, Oscar (Silesian Statistical Reviev, 2016)
The early development of university statistics, or Staatswissenschaft, is briefly sketched, as well as its changing state in the second half of the 19th century, and note that it is still in existence, although in a changed way. In this paper there were also described the work of Karl Fedorovich Gherman (Carl Theodor Hermann) (1809) and a booklet by Christian von Schlözer (1827), the son of A.L. Schlözer
Śląski Przegląd Statystyczny = Silesian Statistical Review, 2016, Nr 14 (20), s. 7-25
Keywords: history of statistics; Göttingen; Achenwall; Schlözer; historia statystyki